Prescription for Division ; Back Home ; Wet, Wild and Wooly [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
The controversy on the six medical students of the U.P. College of Medicine; Filipino overseas contract workers in the Middle East who went home due to the gulf war; Malabon Zoo, owned and managed by Manny Tangco.
Prescription for Division (20 min.) -- Back home (20 min.) -- Wet, wild and wooly (15 min.).
VHS.
Reporter, Luchi Cruz-Valdes.
Keywords: University of the Philippines (Manila). -- College of Medicine -- Admission; University of the Philippines (Manila). -- College of Medicine -- Entrance requirements; Filipinos -- Employment -- Arab countries; Malabon Zoo